2019
DOI: 10.1002/cti2.1100
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of CD103+ CD8+ T cells in a cutaneous melanoma micrometastasis

Abstract: Objective The immune system can halt cancer progression by suppressing outgrowth of clinically occult micrometastases in a state of cancer‐immune equilibrium. Cutaneous melanoma provides a unique opportunity to study the immune contexture of such lesions, as miniscule skin metastases are accessible to clinical inspection and diagnostic biopsy. Methods Here, we analysed by multiplex immunofluorescence microscopy samples from a melanoma patient presenting with an overt and an occult in‐transit metastasis (ITM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In line with this, we and others have recently shown that genetic deletion of Ptpn2 in total T cells, CD8 + T cells or chimeric antigen receptor T cells augments cancer immunity ( LaFleur et al, 2019 ; Wiede et al, 2020 ). In case of cutaneous melanoma, Ptpn2 deficiency indeed results in enhanced generation of tumor-specific CD69 + CD103 + T RM cells ( Wiede et al, 2020 ), and we have previously shown that these cells can drive long-term melanoma control ( Edwards et al, 2018 ; Hochheiser et al, 2019 ; Park et al, 2019a ). Thus, while Ptpn2 modulates the generation of memory precursor cells in a context-dependent manner, it does not appear to influence the process of T RM cell differentiation in peripheral tissues per se.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we and others have recently shown that genetic deletion of Ptpn2 in total T cells, CD8 + T cells or chimeric antigen receptor T cells augments cancer immunity ( LaFleur et al, 2019 ; Wiede et al, 2020 ). In case of cutaneous melanoma, Ptpn2 deficiency indeed results in enhanced generation of tumor-specific CD69 + CD103 + T RM cells ( Wiede et al, 2020 ), and we have previously shown that these cells can drive long-term melanoma control ( Edwards et al, 2018 ; Hochheiser et al, 2019 ; Park et al, 2019a ). Thus, while Ptpn2 modulates the generation of memory precursor cells in a context-dependent manner, it does not appear to influence the process of T RM cell differentiation in peripheral tissues per se.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of tumor-resident CD8 + , CD103 + T cells have been shown to predict treatment response in patients treated with immune checkpoint inhibitors [119]. Furthermore, a case report corroborated that TRMs were involved in melanoma cancer-immune surveillance and cancer-immune equilibrium [31]. CD8 + CD103 + TRM cells bearing the marker CD39, which is involved in immunosuppression, have been found in increased numbers in melanomas compared with a variety of other tumor types [32].…”
Section: Melanomamentioning
confidence: 90%
“…NK cells and tissue-resident CD8 + T cells prevent outgrowth of metastases in murine and human melanoma models (Fig. 2B) [129][130][131]. The effect is postulated to be rather cytostatic than cytotoxic [61].…”
Section: Mechanisms Of Melanoma Dormancy Induction and Reawakeningmentioning
confidence: 95%